Pengaruh Ekspor dan Impor China terhadap Pertumbuhan Ekonomi Indonesia dengan Kurs sebagai Variabel Intervening - Ghina Zulzilah; Muhammad Sri Wahyudi; Setyo Wahyu (Jurnal Ilmu Ekonomi, 2022)
This study aims to determine the direct and indirect effects of China's exports and imports on Indonesia's economic growth through the exchange rate during 2000-2019. The method used is a quantitative approach using secondary data obtained from the publications of the Central Statistics Agency (BPS), World Bank Data, and the International Monetary Fund (IMF). The analytical tool used is path analysis. Data is processed through E-views. The results of this study show that directly Indonesia-China exports had a positive and significant impact on Indonesia's economic growth. While, directly Indonesia-China imports did not have a significant effect on Indonesia's economic growth. Indirectly Indonesia-China exports and imports have no significant effect on Indonesia's economic growth through the exchange rate.